The Etiquette Of Greeting: Opinion Of Jurists - Mohd Safri, Ali; Abdulsoma, Thoarlim; Mohammed Muneer'deen, Olodo Al-Shafi'i (2016)
Contemporarily, many factors have put bars between man and his fellows, most especially when security of life is taken into consideration. Everyone is always selfconscious; fellows and neighbours no more trust themselves and meaningful societal relationship is at stake. The most human factor easily relating one person to the other is greeting, but it has unfortunately been made to look as a private commodity whereby people are free to give it to whomever they want and deny it hosts of others. Those who do greet are seen as primitives and conservatives. It is time to tell what greeting is and what role and influence it plays in uniting the humanity at large, most particularly from the Islamic juristic perspective. This paper wishes to showcase the roles greeting play in ascertaining security of life and property on one hand, and how it helps strengthening and uniting humanity on the other hand. The major sources for the paper are from the Qur’an and Prophetic traditions.